Every day a good day fifteen lessons I learned about happiness from Japanese tea culture - Morishita, Noriko 1956-; Goldsmith, Eleanor 1976- (2019)
"Reporter and essayist Morishita Noriko reflects on twenty-five years of studying the Japanese Way of Tea, from her first uncertain steps as a college student to her gradual discovery of freedom within the very rules that once seemed to hold her back. As Morishita experiences the trials and triumphs of adult life, from job-hunting setbacks to lost love, from the struggle to build a career to the pain of losing a loved one, Tea is always there to remind her that simply being present in the moment is enough. The joy of savoring the seasons with all five senses--of smelling the rain, of hearing each individual raindrop. The importance of cherishing each meeting as a once-in-a-lifetime opportunity. Humor and heartbreak, despair and determination--in this memoir, Morishita vividly connects the Way of Tea to the full span of human experience, culminating in the exhilaration of realizing 'I'm alive, right now!'" -- Publisher's description
Learn that you know nothing -- Don't think with your head -- Focus your feelings on the now -- Watch and feel -- Look at many real things -- Savor the seasons -- Connect to nature with all five senses -- Be here, now -- Give it time and let nature do the rest -- Things are fine as they are -- Parting is inevitable -- Listen for the voice within -- When it's raining, listen to the rain -- Growth takes time -- Live in the moment with an eye to the future.
Originally published in Japanese in 2002.
Translated from the Japanese.
Keywords: Morishita, Noriko -- 1956-.; Japanese tea ceremony; Philosophy, Japanese; Chado